2022
DOI: 10.3389/fcimb.2022.828439
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interferon-Induced Protein With Tetracopeptides (IFITs) Reduces Mycobacterial Growth

Abstract: ObjectivesThe host immune response towards Mycobacterium tuberculosis (M. tb) is known to vary with the virulence of mycobacterial species. While the majority of M. tb-exposed individuals develop latent TB infection (LTBI), a small proportion develops active TB disease. The milieu of understudied immune factors is believed to play an important role against host immune response towards mycobacteria. Here, we investigate the role of antiviral factors of the interferon-induced proteins with tetracopeptides (IFITs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…IFIT family genes are typically expressed at low levels without stimulation, and IFIT is typically transcriptionally induced in response to viral and bacterial infections, participating in the regulation of innate immune responses, and limiting various viruses, stimulating apoptosis of infected cells, and regulating immune responses (Fensterl and Sen 2015 ). Studies have shown that IFIT1, IFIT2, and IFIT3 are upregulated during latent TB infection, and overexpression of IFIT genes in macrophages leads to a striking increase in key pro-inflammatory cytokines, which can ultimately kill Mtb (Madhvi et al 2022 ). OAS, or 2’-5’-oligoadenylate synthetase, is a protein family that encompasses OAS1, OAS2, OAS3, and OASL proteins, which are also a type of interferon-induced gene (Leisching et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…IFIT family genes are typically expressed at low levels without stimulation, and IFIT is typically transcriptionally induced in response to viral and bacterial infections, participating in the regulation of innate immune responses, and limiting various viruses, stimulating apoptosis of infected cells, and regulating immune responses (Fensterl and Sen 2015 ). Studies have shown that IFIT1, IFIT2, and IFIT3 are upregulated during latent TB infection, and overexpression of IFIT genes in macrophages leads to a striking increase in key pro-inflammatory cytokines, which can ultimately kill Mtb (Madhvi et al 2022 ). OAS, or 2’-5’-oligoadenylate synthetase, is a protein family that encompasses OAS1, OAS2, OAS3, and OASL proteins, which are also a type of interferon-induced gene (Leisching et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL2, CXCL10 and CCL2), interleukins (eg. IL1A, IL1B, IL16) and members of TNF superfamily (TNFSF10 and TNFSF11) can promote secretion of proinflammatory cytokines and MMPs ( Kim et al., 2005 ; Ovstebø et al., 2008 ; Madhvi et al., 2022 ), interfere in pathogen replication by either inducing apoptosis or ubiquitin mediated proteasomal degradation ( Zhang et al., 2021 ), induce chemotaxis of leucocytes ( Dinarello, 2018 ) and directly act as antimicrobials ( Yang et al., 2003 ). To contain the bacterial infection, which has a short doubling time ( Neisseria has only 30 min), an aggravated inflammatory response is essential; however, at the BBB level, such response may compromise barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of exacerbated proinflammatory effects may favour the outcome of the disease, diminishing tissue damage and severe complications. While interferons and interferon-inducible proteins like IRF7, IFIT1, and IFIT3 are primarily associated with antiviral defence [ 30 ], they can also be induced in response to bacterial ligands, contributing to the resolution of the infection [ 31 , 32 ]. However, the specific contribution of these factors in combating Pasteurella infections is not fully understood.…”
Section: Discussionmentioning
confidence: 99%